COVID-19-Induced Changes in the Fibrin Network of Pulmonary and Renal Microthrombi - Manuel, Meneses-Flores; Jose, S. Lopez-Gonzalez; Eduardo, Becerril-Vargas; Saray, Santos-Torres; Francina, Bolaños-Morales; Dolores, Aguilar-Cazares; Cesar, Luna-Rivero (International Journal of Coronaviruses, 2024)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection often causes coagulation disorders that affect highly vascularized organs, such as the lungs and kidneys. Objective The objective of this study was to report the histopathological findings of variations in the fibrin pattern of pulmonary and renal microthrombi in patients who died from SARS-CoV-2 infection. Methods Minimally invasive autopsies were performed on 40 patients to collect lung (n=40) and kidney (n=16) tissue samples. Histochemical and immunohistochemical staining techniques were used for histopathological analyses. Premortem laboratory data were obtained from the patients' electronic medical records. Results The lung tissue showed a patchy pattern, characterized by areas of both minimal and severe damage. The most significant histopathological finding was the detection of thrombi with fibrin structures organized into discrete star-shaped units, which were more frequently observed in areas with severe lung injury than in those with minimal lung injury (p = 0.012). Star-shaped fibrin structures were also observed in the renal glomerular capillaries. Immunohistochemical staining revealed the presence of platelets and the procoagulant proteins von Willebrand factor (VWF) and Factor VIII within the star-shaped fibrin thrombi. Patients with star-shaped fibrin thrombi had higher levels of the systemic inflammatory indicators C-reactive protein (CRP) and neutrophil-to-lymphocyte ratio (NLR). Conclusion Our observations suggest that the inflammatory microenvironment resulting from SARS-CoV-2 infection may contribute to the formation of star-shaped fibrin units in the pulmonary and renal microthrombi.
Keywords: SARS-CoV-2; Autopsy; Lung; Kidney; Microthombi; Fibrin Network